An Efficient and Mild Oxidation of Thiols to Disulfides with Tributylammonium Chlorochromate - GHAMMAMY, SHAHRIARE (Asian Journal of Chemistry, 2010)
Various kinds of aliphatic and aromatic thiols are converted into the corresponding disulfides by tributyl ammonium chlorochromate in excellent yields under different reaction conditions.